The Effect of Early Mobilization on Incerased Intestinal Peristaltic Post Sectio Caesarea at Grandmed Lubuk Pakam Hospital in 2023 - Simarmata, Juni Mariati; Syatriawati, Syatriawati; Padila, Della (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Sectio Caesarea is a surgical process with the aim of removing the fetus through an incision in the abdominal wall which is connected to the autonomic nervous system, so that bowel movements become slow and cause problems. Caesarean section deliveries are increasingly being performed and their success is high, although they are still considered the last solution. Cesarean section operations are common for mothers who are about to give birth. So that post-operative intestinal peristalsis can return immediately, mobilization is necessary. If there is no mobilization, the motility function of the intestines and bladder will take a long time to return to normal so that the mother will have difficulty defecating. This research aims to measure how much mobilization increases intestinal peristalsis in post-caesarean section surgery patients. The research is quantitative research with a One Group pre-post test design. The sample consisted of 25 post-cesarean section mothers with primigravida births. The instruments used are SOP sheets and observations. Data analysis using the Paired T-test with an error of 0.05 showed that the average intestinal peristalsis before the intervention was 7.20 while after the intervention it was 8.04. The results of the Paired T-test show that the p-value is 0.000, which means that there is an effect of mobilization on increasing intestinal peristalsis in post caesarean section patients at GrandMed Lubuk Pakam Hospital. It is recommended that you always implement post caesarean section mobilization measures in accordance with the SOP.